2019
DOI: 10.5114/pm.2019.84157
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in postmenopausal women – causes, symptoms, treatment

Abstract: Urinary incontinence (UI) is an important social problem that affects more than 50% of postmenopausal women. The number of patients increases from year to year. According to recent data, UI affects women twice as often as men. This condition occurs in about 20-30% of young women, 30-40% in middle age and up to 50% of women in old age. There are five types of urinary incontinence. The etiology of the problem of incontinence is not fully understood, because the problem can affect men and women of all ages and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 25 publications
1
35
0
12
Order By: Relevance
“…The grades of SUI are as follows: grade 1, urinary outflow will occur only when negative pressure is increased such as laughter, coughing, sneezing, etc. ; grade 2, urine outflow occurs during nonviolent normal activities such as standing and walking; grade 3, under rest, bed rest, and other resting states, urine flows out spontaneously ( Kołodyńska et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The grades of SUI are as follows: grade 1, urinary outflow will occur only when negative pressure is increased such as laughter, coughing, sneezing, etc. ; grade 2, urine outflow occurs during nonviolent normal activities such as standing and walking; grade 3, under rest, bed rest, and other resting states, urine flows out spontaneously ( Kołodyńska et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of SUI has gradually increased with the global aging, recent studies have reported that SUI has become one of the world's five major chronic diseases 23,24 . SUI compromises patients' ability of social, sexual life and psychology health level, thereby reducing patients' quality of life 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence has been found in 50% of postmenopausal women. The high incidence of urinary incontinence in menopausal women is due to estrogen defi ciency 18 .…”
Section: Discussionmentioning
confidence: 99%